Towards greater regulatory co-operation in the Asia-Pacific for boosting e-commerce trade - Arpita Mukherjee; Ketaki Gaikwad; Aahana Srishti (Indian Council for Research on International Economic Relations (ICRIER), 2024)
The Asia-Pacific (APAC) region, which accounts for over 50 per cent of the world's population and over 35 per cent of the world's gross domestic product (GDP), is one of the fastest growing regions in the world. The region is growing at higher than the global growth rate and is expected to continue on a high growth trajectory. With high economic growth, the APAC region has become the largest e-commerce market in the world. The e-commerce sector in APAC was valued at US2.9 trillion in 2022 and is projected to reach at value of US6.146 trillion by 2030, accounting for a share of more than half the global retail e-commerce market. Rapid urbanisation, along with rise in incomes and technological developments (such as 4IR technologies), have led to the growth of e-commerce in the region. A policy push towards digitalisation by key countries and the coronavirus (COVID-19) pandemic has further facilitated the growth of e-commerce in this region with consumers and micro, small and medium enterprises (MSMEs) increasingly using e-commerce platforms. Producers and exporters are now using e-commerce platforms to enhance their global reach. In many countries, governments have come up with initiatives to support the use of e-commerce platforms by MSMEs for exports. The sudden growth of e-commerce disrupted traditional supply chains in the APAC region and created the need for a robust and predictable regulatory environment to facilitate the ease of doing business, both domestic and cross-border, while simultaneously addressing issues like consumer safety and privacy. Therefore, e-commerce is now a key component of all new age trade agreements. However, there is neither a framework nor strategy for regulatory co-operation, policy dialogue, initiatives and sharing of best practices at the APAC level to facilitate more cross-border trade. Given this background, the objective of this paper is to (a) examine the growth of e-commerce in the Asia-Pacific region, (b) identify the growth drivers and the contribution of the sector to MSMEs, women entrepreneurs, and allied sectors like express delivery services, (c) examine the policy landscape and how it is evolving in APAC countries with a focus on learning from each other's best practices (d) identify the policy and other challenges such as those related to cross-border data sharing, consumer privacy, crossborder payments, gaps in paperless trade, etc., that may impact the current and/or future growth of the e-commerce sector and its users and (e) make recommendations to facilitate cross border e-commerce trade and help users of e-commerce platforms like MSMEs and women entrepreneurs enhance their global reach.
Keywords: L81; F13; F15; F23; 330; Asia-Pacific; E-commerce; Trade; Policy; MSMEs